HUBUNGAN DAYA LEDAK OTOT LENGAN-BAHU DAN KEKUATAN OTOT TUNGKAI DENGAN KETEPATAN TERHADAP PUKULAN SMASH PADA EKSTRAKURIKULER PUTRI SMP NEGERI 4 TAMBANG KECAMATAN TAMBANG - Wahyudi Wahyudi; Zainur Zainur; Ardiah Juita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: The purpose of this study was to determine the relationship between arm-shoulder muscle explosive power and leg muscle strength with smash accuracy in female badminton extracurricular at SMP Negeri 4 Tambang, Tambang District. It was carried out in the field of SMP Negeri 4 Tambang, Tambang District on November 20, 2019 to November 23, 2019. The population in this study were female badminton extracurricular students of SMP Negeri 4 Tambang, Tambang District who actively participated in badminton extracurricular activities, with a sample of 21 people. This research was taken through arm muscle explosive power test, leg muscle strength measurement test, Smash accuracy. Data collection This research was conducted using a correlation research design. Data analysis was carried out using product moment correlational analysis statistics. Before the data was analyzed, the normalization test was carried out with the Lilliefors test. From the results of the study, it was concluded that there was a relationship between arm and shoulder muscle power with smash accuracy on women's badminton extracurricular at SMP Negeri 4 Mining, where rcount (0.550) > rtable (0.532). There is no correlation between muscle strength and smash accuracy in women's badminton extracurricular at SMP Negeri 4 Mining, where rcount (0.048) > rtable (0.532). There is a relationship between arm and shoulder muscle strength and muscle strength with the accuracy of the extracurricular smash of women's badminton at SMP Negeri 4 Mining, where rcount (0.550) > rtable (0.532). So the results obtained from this study that the physical condition is good enough to get the accuracy of badminton smash. From several physical conditions, the variables are arm and shoulder muscle power and leg muscle strength. Key Words: Arm-shoulder explosive power, leg muscle strength, smash hit accuracy